Integrative Model Of The Effect Of Competence And Individual Behavior On Employee Performance Through Work Motivation - Romasta Napitupulu; Herman Paleni; Yohanes Susanto; Noorchamid Ustadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research is motivated by the importance of improving employee performance within government agencies, which is not only influenced by structural factors but also by competence, individual behavior, and work motivation. This study aimed to analyze the effect of competence and personal behavior on employee performance, with work motivation as an intervening variable at the Research and Development Agency of Musi Rawas Regency. This research uses a quantitative approach with descriptive methods. The sample comprised 42 respondents, determined through the saturated sampling technique. Data collection was done through questionnaires and data analysis using the path analysis method with the help of the SmartPLS version 4.0 application. The results showed that competence and individual behavior positively and significantly affected performance, both partially and simultaneously. Work motivation is proven to mediate the relationship significantly. These findings indicate that positive individual competencies and behaviors can optimally improve employee performance if supported by high work motivation. Therefore, good human resource management that emphasizes the development of aspects of competence, behavior, and motivation is an essential strategy for increasing the effectiveness of public organizations.